2017
DOI: 10.1111/cyt.12496
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of diagnostic criteria associated with atypical breast cytology

Abstract: Interobserver and intraobserver variability remains a significant challenge for cytologists. Despite attempts to define significant criteria associated with C3, good reproducibility could not be achieved. The C3 category is imprecise and highlights the inadequacy of the current classification reporting categories for breast FNA. The impending review of reporting breast cytology by the International Academy of Cytology is timely and appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…1 They used j index and reported that the interobserver agreement was poor for all criteria except tubules which performed badly also, the intraobserver variability for the two cytologists showed that one cytologist achieved moderate intraobserver agreement for all the criteria except cohesion which was poor, whilst the second cytologist showed poor agreement for all criteria. The purpose of the authors was to assess the interobserver and intraobserver variability when identifying the cytological criteria, which were found to have a statistically significant association with C3 within a workplace environment.…”
Section: Dear Editormentioning
confidence: 99%
“…1 They used j index and reported that the interobserver agreement was poor for all criteria except tubules which performed badly also, the intraobserver variability for the two cytologists showed that one cytologist achieved moderate intraobserver agreement for all the criteria except cohesion which was poor, whilst the second cytologist showed poor agreement for all criteria. The purpose of the authors was to assess the interobserver and intraobserver variability when identifying the cytological criteria, which were found to have a statistically significant association with C3 within a workplace environment.…”
Section: Dear Editormentioning
confidence: 99%
“…ing cytological criteria associated with 'atypical' diagnoses. 56 Even in these cases, however, poor agreement values were observed for all criteria (presence of myoepithelial cells, cohesiveness, cystic background, papillary fragments and tubular structures), thereby highlighting the morphological complexity of this indeterminate category.…”
Section: Weigner Et Al Who Assessed Interobserver Variability In Iden...mentioning
confidence: 83%
“…We thank Naderi and Sabour for their interest in our article . They question the statistical methodology we employed in our article.…”
mentioning
confidence: 99%
“…They question the statistical methodology we employed in our article. We would like to point out that the aim of our study was to assess interobserver and intraobserver variability when identifying the cytological criteria, which were found to have a statistically significant association with C3 within a workplace environment …”
mentioning
confidence: 99%